Montelukast during Primary Infection Prevents Airway Hyperresponsiveness and Inflammation after Reinfection with Respiratory Syncytial Virus - Han, Junyan (American Thoracic Society, 2010)
Rationale: Respiratory syncytial virus (RSV) bronchiolitis in infants may be followed by the development of asthma-like symptoms. Age at first infection dictates consequences upon reinfection. Reinfection of mice initially exposed as neonates to RSV enhanced development of airway hyperresponsiveness (AHR), eosinophilic inflammation, and mucus hyperproduction. RSV lower respiratory tract disease is associated with activation of the leukotriene pathway. Objectives: To determine the effects of montelukast (MK), a cysteinyl leukotriene (cysLT) receptor antagonist, in primary and secondary RSV-infected newborn and adult mice. Methods: BALB/c mice were infected with RSV at 1 week (neonate) or 6 to 8 weeks (adult) of age and reinfected 5 weeks later. MK was administered 1 day before the initial infection and through Day 6 after infection. Seven days after primary or secondary infection, airway function was assessed by lung resistance to increasing doses of inhaled methacholine; lung inflammation, goblet cell metaplasia, and cytokine levels in bronchoalveolar lavage fluid were monitored. Measurements and Main Results: RSV infection induced cysLT release in bronchoalveolar lavage fluid. MK decreased RSV-induced AHR, airway inflammation, and increased IFN-γ production in primary infected adult and neonatal mice. MK, administered during initial infection of neonates but not during secondary infection, prevented subsequent enhancement of AHR, airway eosinophilia, and mucus hyperproduction upon reinfection. Conclusions: MK attenuated the initial responses to primary RSV infection in both age groups and altered the consequences of RSV reinfection in mice initially infected as neonates. These data support an important role for cysLT in RSV-induced AHR and inflammation.